2015
DOI: 10.1037/pas0000118
|View full text |Cite
|
Sign up to set email alerts
|

Does assessing suicidality frequently and repeatedly cause harm? A randomized control study.

Abstract: Assessing suicidality is common in mental health practice and is fundamental to suicide research. Although necessary, there is significant concern that such assessments have unintended harmful consequences. Using a longitudinal randomized control design, we evaluated whether repeated and frequent assessments of suicide-related thoughts and behaviors negatively affected individuals, including those at-risk for suicide-related outcomes. Adults (N = 282), including many diagnosed with Borderline Personality Disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 36 publications
4
61
1
Order By: Relevance
“…Recent advances in technology, particularly with respect to mobile phones, have made it increasingly possible to investigate the occurrence and precursors of SI and behavior in real‐time via Ecological Momentary Assessment (EMA), which involves repeated and frequent assessment of behavior in the person's natural environment (Moskowitz & Young, ; Shiffman, Stone, & Hufford, ). Existing studies involving repeated assessment of suicide risk‐related constructs have demonstrated that EMA data collection is feasible (Davidson, Anestis, & Gutierrez, ) and that repeated assessment of suicidal thoughts was not associated with any iatrogenic increase in suicidal thinking (Husky et al., ; Law et al., ). Additional EMA studies with adults have indicated that suicidal thoughts are dynamic over short periods of time, sometimes fluctuating over an interval of only a few hours (Hallensleben et al., ; Kleiman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in technology, particularly with respect to mobile phones, have made it increasingly possible to investigate the occurrence and precursors of SI and behavior in real‐time via Ecological Momentary Assessment (EMA), which involves repeated and frequent assessment of behavior in the person's natural environment (Moskowitz & Young, ; Shiffman, Stone, & Hufford, ). Existing studies involving repeated assessment of suicide risk‐related constructs have demonstrated that EMA data collection is feasible (Davidson, Anestis, & Gutierrez, ) and that repeated assessment of suicidal thoughts was not associated with any iatrogenic increase in suicidal thinking (Husky et al., ; Law et al., ). Additional EMA studies with adults have indicated that suicidal thoughts are dynamic over short periods of time, sometimes fluctuating over an interval of only a few hours (Hallensleben et al., ; Kleiman et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The patient especially stressed the fact that the SNS did in no way increase her suicide risk. This is in line with studies not reporting harmful effects of monitoring suiciderelated variables in high-risk patients (Clum and Curtin, 1993;Husky et al, 2014;Law et al, 2015). Instead, the patient experienced the daily completion of the questionnaire as a helpful routine, sometimes as an obligation, sometimes as a pastime, and sometimes it was difficult to find the appropriate answers.…”
Section: Discussionmentioning
confidence: 53%
“…In some suiciderelated monitoring studies there were several (2-6) assessments per day (Links et al, 2007;Nock et al, 2009;Palmier-Claus et al, 2012Husky et al, 2014;Law et al, 2015). Several other relevant studies used a daily sampling scheme (Clum and Curtin, 1993;Witte et al, 2006;Thompson et al, 2014;Restifo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect included in the UWRAP is the pre-to postassessment procedure, which is designed to evaluate potential distress and suicidal urges that may have been elicited by the assessment. Indeed, while previous research has consistently found that participation in research, even in-depth interviews, may temporarily increase emotional distress for some participants, but does not increase suicide risk (e.g., Eynan et al, 2014;Jorm, Kelly, & Morgan, 2007;Law et al, 2015;Reynolds et al, 2006), there are instances in which individuals may experience elevated suicidal urges, for which suicide risk management procedures should be implemented. Therefore, given the urgent need to bring more researchers into the field of suicide research, we describe the implementation of a suicide risk and management protocol (the UWRAP) in the context of two different randomized clinical trials.…”
mentioning
confidence: 99%